On Necessary and Sufficient Conditions for the Asymptotic Stability of Impulsive Systems - Ignat'ev, A. O.; Gladilina, R. I. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We prove that the sufficient conditions for the asymptotic stability of impulsive systems obtained by Gurgula and Perestyuk are also necessary conditions.